Cenários e adaptações das organizações ao Second Life - Sandi, André Quiroga (Universidade do Vale do Rio do Sinos, 2009)
This study investigates the technological appropriation carried out by organizations in interactive 3D virtual spaces aiming at the upgrading of its communications processes, which is a real need when it comes to competitive insertion within society. In doing so, it states, as a starting point, that such appropriation inserts organizations in the movement between virtual/ real, currently existent in spaces made possible by computer- mediated technologies and techniques, contributing to the construction of organizational acknowledgement in a media space characterized by adapting processes. It aims to understand the organizational spaces present in Second Life through digital sceneries, modeled by image synthesis which convey a virtual and real interweaving, feasible by computational technological mechanisms and devices. The methodological support used is the netnography, a field borne out of anthropology whose focus is the understanding of the dynamics of virtual spaces and the computer-mediated communications
Keywords: cenários digitais; Second Life; comunicação organizacional; virtual spaces; organizational communication; Ciências Sociais Aplicadas